2019
DOI: 10.1016/j.tjem.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes in right ventricular metastatic cardiac tumor mimicking acute ST elevation myocardial infarction: A case of misdiagnosis

Abstract: IntroductionIn patients with ST elevation myocardial infarction (STEMI), minimizing the reperfusion time is the goal of therapy worldwide. However, the differential diagnosis is critical and when a patient is encountered with chest pain and ST elevation, STEMI should not be the only diagnosis considered. By detailed history and focused physical examination, it is possible to avoid a mistaken diagnosis.Case presentationIn this report, we present a case of a male patient with tongue cancer and accompanying myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…14) The suggested mechanisms for these ECG patterns are, besides tumor emboli or a lesion surrounding a coronary artery, inflammation around the neoplastic mass, ionic transfer of potassium from necrotic tissue, neoplastic stretch of adjacent muscle fibers, or pericardium invasion. [14][15][16] In addition, apart from sinus tachycardia, abnormal axis pattern, right bundle branch block, ST depression, or T-wave inversion, STE in precordial leads is found in approximately 5% of the cases of APE, and it is related with poor diagnosis. 17,18) The underlying mechanism for STE in APE is not very clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14) The suggested mechanisms for these ECG patterns are, besides tumor emboli or a lesion surrounding a coronary artery, inflammation around the neoplastic mass, ionic transfer of potassium from necrotic tissue, neoplastic stretch of adjacent muscle fibers, or pericardium invasion. [14][15][16] In addition, apart from sinus tachycardia, abnormal axis pattern, right bundle branch block, ST depression, or T-wave inversion, STE in precordial leads is found in approximately 5% of the cases of APE, and it is related with poor diagnosis. 17,18) The underlying mechanism for STE in APE is not very clear.…”
Section: Discussionmentioning
confidence: 99%
“…3,26) Owing to their rarity and poor outcome, cardiac tumors, especially presented with symptoms and ECG changes mimicking myocardial infarction, represent a challenging clinical problem, and there is still no clear advice on the treatment process. 15,22) Considering that the operative mortality rate of such patients is extremely high and that metaplastic breast cancer is characterized by a very poor response to most systemic chemotherapy, the literature underlines the role of palliative care, including local radiotherapy, chemotherapy, and analgesic treatment. 3,7,23) It is suggested that if cardiac involvement is leading to coronary artery occlusion or compression causing ischemic symptoms, surgical resection, radiation therapy, or coronary angiography should be considered in clinically stable patients with a relatively favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We consider this case important to report because the patients in most of the previously documented cases presented with cardiopulmonary symptoms. For example, a case reported by Demir et al in January 2019 described a 59-year-old man with a history of tongue cancer who presented to the emergency department for acute-onset chest pain [ 4 ]. The ECG demonstrated ST-segment elevation in leads V1-V6 consistent with acute anterior wall myocardial infarction and the patient was found to have a large tumor involving the right ventricular free wall on TTE.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have been published on ST-segment changes in the context of cardiac tumors, though the precise pathophysiological mechanism behind the ECG changes continues to be debated. Suggested hypotheses for these changes include embolization of tumor fragments to coronary arteries, external compression of coronary arteries, distension of cardiac muscle fibers, peri-tumor inflammatory reactions, and electrolyte transfer from necrotic tumor tissue to adjacent myocardium [ 4 , 5 ]. Regardless of the particular mechanism involved, most documented cases of ST-segment elevation in the setting of cardiac tumors often appear to present with chest pain/discomfort or clinical signs of developing heart failure [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation